Facilitators and barriers to health enhancing physical activity in individuals with severe functional limitations after stroke: A qualitative study - Reicherzer, Leah; Wirz, Markus; Wieber, Frank; Graf, Eveline S. (Frontiers in Psychology, 2022)
Background: Patients with chronic conditions are less physically active than the general population despite knowledge of positive effects on physical and mental health. There is a variety of reasons preventing people with disabilities from achieving levels of physical activities resulting in health benefits. However, less is known about potential facilitators and barriers for physical activity in people with severe movement impairments. The aim of this study was to identify obstacles and facilitators of physical activity in individuals with severe disabilities. Methods: Using a qualitative approach to explore individuals’ subjective perspectives in depth, five community-dwelling adults (age 52-72, 2 female, 3 male) living with chronic mobility impairments after stroke that restrict independent physical activity were interviewed. A semi structured topic guide based on the theoretical domains framework was utilized. The interview data was analyzed thematically, and the theoretical domains framework constructs were mapped onto the main and sub-categories. Results: The six main categories of facilitators and barriers along the COM-B framework were:1) physical capabilities, 2) psychological capabilities, 3) motivation reflective, 4) motivation automatic, 5) opportunity physical, 6) opportunity social. The physical capabilities to independently perform physical activity were variable between participants but were not necessarily perceived as a barrier. Participants were highly motivated to maintain and/or increase their abilities to master their everyday lives as independently as possible. It became clear that a lack of physical opportunities, such as having access to adequate training facilities can present a barrier. Social opportunities in the form of social support, social norms or comparisons with others can act as both facilitators and barriers. Conclusion: While confirming known barriers and facilitators that impact the ability of individuals with functional limitations to be active, the findings highlight the need and opportunities for comprehensive service models based on interdisciplinary collaborations.